THE FORMATION HISTORY OF THE ARMENIAN–AZERBAIJANI BORDER LINE ACCORDING TO SOVIET TOPOGRAPHIC MAPS (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
The article introduces the changes of the Armenian–Azerbaijani borders according to the 1920–1990s Soviet topographic maps. Several dozen maps published in those years have been visually studied. The monitoring of the border lines reflected on the maps proves that the territory of Armenia has continuously shrunk during the aforementioned period. In order to calculate the precise amount of loss, it is recommended to use geo-information technologies.
Keywords: territory of RA; topographic maps; Armenian-Azerbaijani border; border line; enclave